The Influence of Educational Infrastructure in Agricultural Learning Environment on Students’ Interest and Program Selection - M.I., Nur Dinie; M.S.K, Enio (Journal of Technical Education and Training, 2023)
There is a growing global concern in agricultural education due to past findings on students’ lack of interest in studying and considering a career in agriculture. In spite of this, past local studies have shown an agricultural-related careers are getting more interest from students due to the practical learning environment provided by the Universiti Putra Malaysia (UPM) Agricultural Science Foundation (ASPer UPM) but there is no thorough explanation regarding the elements of practical learning environment that affects students’ interest. This qualitative study was to provide additional insight into the learning infrastructure as a component of the agricultural subjects’ practical learning environment by examining how infrastructure in agricultural practical learning environment influences students’ interest and selection of agriculture as a field of study. Furthermore, it attempts to identify students’ perceptions of practical learning infrastructure as part of the ASPer UPM learning environment. This qualitative study collected data through the focus group interview using an interview questions instrument. The study found that students perceive the provision of infrastructure and equipment as not uniform, and the technology adopted is inadequate and only sufficient to help with basic work. The students also perceive the instructors’ expertise and specialisation as helping them understand the course content and the specialised locations are aligned with the learning content. The study found that students’ interest could be increased by changing the learning location and content, providing adequate, usable and conducive infrastructure and implementing clear teaching and practical learning procedures. At the same time, infrastructure can generate curiosity, provide early exposure to agriculture and change negative perceptions and interests to influence students to select agriculture as a field of study. Lastly, this study found an apparent relationship between Faculty of Agriculture cluster students’ selection of fields of study and their foundation course CGPA. These results can be utilised as guidance for agricultural education institutions to design a high-quality practical learning environment via enhanced infrastructure.